THE USE OF OPEN ENDED LEARNING MODELS IN TERMS OF STUDENTS' MATHEMATICAL CREATIVE THINKING ABILITY - anwar sidiq; Dwi Desmayanasari; Noprisa Noprisa; Suryatul Aini Asyhara; Deni Efendi (Universitas Muhammadiyah Lampung, 2022)
This research aimed to find out the differences of the improvement of students mathematical creative thingking skill using open ended. This research used quasi experimental method whith pretest-posttest control group. The subjects of this research were 60 students at class VII in one of the MTs in Bandar Lampung city. There are two classess in this study namely the experimental class consisted of 30 students getting open ended learning models and the second control class consisted of student getting scientific approach. The instrument of this study used student creative thingking skill test, based on mathematical creative thingking indicator. The result of this study showed all of improvement of mathematical creative thingking students ability getting open ended learning model was not better then students getting scientific approach.